Up-regulation of blood-circulating TIM-4-expressing monocytes and potential diagnostic biomarker sTIM-4 in primary liver cancer - Yifeng Yang; Yan Wei; Yilian Zhao; Chao Ye; Dan Zeng; Xiaoxing Zhou; Mengru Xie; Xingcai Chen; Jilin Qing; Zhizhong Chen (Scientific Reports)
Abstract Primary hepatocellular carcinoma (PHC) remains a globally prevalent malignancy, where early diagnosis is critical. Monocytes have been implicated in tumor progression. This study investigated the expression of T cell immunoglobulin and mucin domain-containing protein 4 (TIM-4/TIMD4) in PHC tissues and peripheral blood monocytes, and assessed the clinical relevance of soluble TIM-4 (sTIM-4). Immunohistochemistry and bioinformatics analyses revealed reduced TIM-4 expression in PHC tissues, which correlated with immune cell infiltration. Flow cytometry showed elevated TIM-4 expression in circulating monocytes of PHC patients, predominantly within the intermediate subset (91.7%). sTIM-4 and monocyte TIM-4 levels were positively correlated with alpha-fetoprotein (AFP), alanine aminotransferase (ALT), aspartate aminotransferase(AST), gamma-glutamyl transferase (GGT), alkaline phosphatase (ALP), and negatively correlated with albumin (ALB). Notably, sTIM-4 levels were significantly higher in patients with a history of hepatitis. Logistic regression indicated that elevated sTIM-4 was associated with a 2.29-fold increased risk of PHC. ROC analysis demonstrated that the combination of sTIM-4 and AFP improved diagnostic accuracy for PHC. In conclusion, TIM-4 is downregulated in PHC tissues but upregulated in circulating intermediate monocytes, suggesting its dual role in tumor immunobiology. The combined measurement of sTIM-4 and AFP enhances diagnostic sensitivity and offers predictive value for PHC risk stratification.